Breaking Barriers: Performance Optimization of Super Big Digger PC2000-8 at PT ABC Using DMAIC Methodology - Samino Samino; Maulahikmah Galinium; Togar Wiliater Soaloon Panjaitan Dena (ILTEK : Jurnal Teknologi, 2026)
This research addresses the suboptimal physical availability (PA) of the PC2000-8 Super Big Digger at PT ABC, a major mining contractor in partnership with PT United Tractors. From January to June 2024, the average PA was only 87.04%, below the target of 92%, posing operational risks and reducing stakeholder confidence. The study applied the DMAIC (Define, Measure, Analyze, Improve, Control) Six Sigma methodology to examine six key maintenance indicators: Periodical Service Achievement, Lead Time Accuracy, Hour Meter Accuracy, Periodical Service Accuracy, Backlog Execution Lead Time, and Start Time Accuracy. Analytical tools such as Fishbone Diagram and Failure Mode and Effects Analysis (FMEA) were used to identify root causes. The analysis revealed high Risk Priority Numbers (RPNs) in the lubrication, air conditioning, and sensor systems. Improvements were implemented through grease injector upgrades, AC component modifications, and enhanced maintenance coordination. Results showed significant improvements in Mean Time to Repair (MTTR), reduced from 4 hours to 1.69 hours, and an increase in PA from 87.04% to 93.77% by July 2025. This study demonstrates that a structured, data-driven DMAIC approach can effectively improve mining equipment reliability and sustain operational performance.